Gamification-based strategies to improve motivation in English learning in university students - Alban Defilippi, María Teresa (2025)
The phenomenon of globalization has consolidated English as a fundamental competence in academic, work and social contexts, demanding innovative strategies that promote motivation and effective learning. This study aims to analyze the impact of gamification-based strategies on the motivation of university students to learn English. To do this, a bibliographic review of research published between 2020 and 2024 in databases such as Scopus, Scielo and Google Scholar was carried out. The methodology included the qualitative analysis of studies that addressed the use of digital platforms and game dynamics, such as Kahoot, Quizizz, educational video games and reward systems, in university contexts. The results showed that gamification significantly increases students' motivation, participation and academic performance. In Mexico, the use of interactive platforms increased student participation by 35%; In Spain, 87% showed sustained interest in the activities over a semester, and in Colombia, a 20% improvement was recorded in vocabulary and grammar tests. These findings demonstrate that gamification transforms traditional environments into dynamic ones, facilitating more contextualized, collaborative and autonomous learning. In conclusion, gamification is positioned as an effective pedagogical tool to improve motivation and results in English teaching, integrating technological and participatory elements that promote meaningful learning and respond to the educational demands of the 21st century.